The Molecular Genetic Peculiarities of Genomic Structure of Members of the Ebolavirus Genus - A. A. Petrov; V. N. Lebedev; L. F. Stovba; T. E. Sizikova; T. M. Plekhanova; O. N. Sidorova; N. S. Pyshnaya; D. I. Paveliev; S. V. Borisevich (Проблемы особо опасных инфекций, 2015)
The molecular genetic peculiarities of genomic structure of the Ebolavirus genus members are viewed in the review. The Ebola virus disease outbreaks in West African countries constitute a threat not only for Africa, but for the whole world in view of possible introduction of the agent in non-endemic regions. The members of the Ebolavirus genus have different pathogenicity for humans, thus differ severity and mortality of the disease they cause. There is a significant genetic divergence among members of the Ebolavirus genus. The differences of pathogenic potential of members of the Ebolavirus genus may be explained as the result of mutations in the genes of virus structural proteins. It is possible, that some of these mutations may affect virulence of strains within one virus species. So far as most effective modern medicines for specific prophylaxis and treatment of Ebola fever are target-oriented, genotyping of the agent will promote elaboration of strategy of such preparations development.